Evaluation of the Application Effect of Virtual Simulation Technology in Rural Garden Landscape Design. (5th August 2022) - Tang, Yuping; Xuan, Yang; Zhu, Xiaoyue
Abstract : In order to improve the effect of rural garden landscape design, this paper combines virtual simulation technology to design rural garden landscape and evaluates its design effect. Moreover, this paper proposes an optical modulation system for the application of virtual simulation in rural garden landscape design. In addition, before the target is modulated, this paper converts the two-dimensional image on the detector target surface into a one-dimensional stretched modulation image so that the beam emitted by each object point is stretched and flattened on the detector target surface. Finally, this paper explores the influence of lens spacing and field of view on the modulation image of the target surface and the characteristics of projected intensity attenuation after modulation and designs a modulation model that optimizes attenuation. The research results show that the garden landscape design based on virtual reality technology proposed in this paper has a good effect and is of great significance to the effect of rural garden landscape design.